Penerapan Metode Copy The Master Dalam Meningkatkan Keterampilan Menulis Cerpen Siswa Kelas XI SMA Negeri 9 Gowa - Eka Purnamasari; Nensilianti; Muhammad Alyafid (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to describe the application of Copy the Master method in improving the short story writing skills of class XI students of SMA Negeri 9 Gowa. The type of research used is Classroom Action Research. The sample in the study were students of class XI.3 SMA Negeri 9 Gowa totalling 30 students. Data collection techniques in this study were observation sheets, test administration, and interviews and documentation. The results of the study of students' ability to write short stories using the Copy the Master method showed an increase in each cycle and qualification was achieved in cycle II by achieving the provisions of the success indicators that must be achieved, namely 75% of students who get a Minimum Completion Criteria score of 78. The learning results of cycle I, namely with a percentage result of 40% or an average result of 69, were different in cycle II which experienced a more effective change with a percentage result of 83% or an average result of 82. Based on the results of this study, it can be concluded that the application of the Copy the Master method in improving the short story writing skills of students in class XI.3 SMA Negeri 9 Gowa was declared successful.